Energizing compassion: using music and community focus to stimulate compassion drive and sense of connectedness - Gilbert, Paul; Basran, Jaskaran Kaur; Plowright, Ptarmigan; Gilbert, Hannah (Frontiers in Psychology, 2023)
Objectives The last 20 years have seen considerable research on the nature and biopsychosocial impacts of compassion training on self and others. This training is usually focused on calming and slowing the mind and body and on individual imagery practices and mantras. This study explored the effects of three variations: 1. The impact of using energizing music to generate activation and “drive” for compassion; 2. To focus on imagining “breathing in and breathing out a white light or mist of compassion” to bring compassion to the world; and 3. While listening to energizing music, participants were guided to imagining connecting to the compassion (Sangha) community, imagining oneself as linking with others as part of communities seeking to help the world. Methods From approximately 1,600 members of the Compassionate Mind discussion list, participants were invited to take part in a new energizing focused self-practice study. The study involved listening to recorded guidance on the evolutionary model of compassion and the need to address the potentially harmful side of our nature. This was followed by a 4 1/2-min tonglen-informed guided practice of breathing in and breathing out compassion accompanied by energizing music. Forty-three participants completed several self-report scales measuring compassion orientation, wellbeing, social safeness, and positive affect before and following 2 weeks of practice. Participant experiences were recorded from 6 open explorative questions. Results Self-report measures taken before and following 2 weeks of practice revealed significant increases in self-compassion, compassion to others, openness to compassion from others, activated positive affect, safe positive affect, social safeness, and wellbeing, with the largest effect size relating to compassion for the self (d = −0.76). In addition, qualitative data revealed that the participants had experienced the practice as energizing, inspiring, and felt socially connected and that it had significant impacts on other aspects of their lives. Some participants noted that engaging with suffering also stimulated sadness. Conclusion This study found that pairing energizing music with breathing practices and specific compassion visualizations, focusing on the desire to bring compassion to the world and be part of a compassionate community, was well-accepted and had a range of significant positive impacts. This study indicates the potential value of exploring energizing in comparison to the more standard soothing and settling practices as ways of stimulating the biopsychosocial processes of compassion.